An Investigation of Liquid Chromatography–Mass Spectral Attributes and Analytical Performance Characteristics of Tenofovir, Emtricitabine and Efavirenz in Human Plasma. (20th October 2015) - Ndolo, Sedireng M.; Sichilongo, Kwenga; Massele, Amos; Sepako, Enoch; Vento, Sandro
Abstract : Liquid chromatography (LC) and mass spectral behavior and analytical performance characteristics of efavirenz (EFV), emtricitabine (EMT) and tenofovir (TFV), i.e., individual components of Atripla ®, were probed. This was followed by estimation of their analytical performance characteristics employing LC and a parallel direct infusion sample introduction procedure. Performance characteristics using both types of sample introduction procedures were compared. Using liquid chromatography–mass spectrometry (LC–MS), linearities, i.e., correlation coefficients of the calibration curves of EFV, EMT and TFV, ranged between 0.9300 and 0.9990 in the full scan, selected ion monitoring and mass spectrometry/mass spectrometry (MS-MS) modes. The limits of detection (LODs) ranged between 0.5 and 11.6 µg/L. The lower limits of quantification (LLOQs) and the upper limits of quantification (ULOQs) were in the ranges of 0.9–23.2 and 1.6–38.7 µg/L, respectively. The LODs ranged between 0.8 and 114.7 µg/L. The LLOQs and the ULOQs were in the ranges of 1.6–29.4 and 2.7–49.0 µg/L, respectively. In the case of EMT, sodiated molecular ion at m / z 270 was used to adduce analytical performance characteristics from which lower detection limits were obtained compared with those in the literature where [M+H] + at m / z 248 was used.